Neonatal outcomes of pregnant women diagnosed with SARS-CoV-2: an integrative review (Research, Society and Development, 2021)
The present study analyzed the neonatal outcomes reported in pregnant women with COVID-19. An integrative review was carried out after formulating the guiding question. That done, the research strategy, selection of criteria and data extraction were carried out. The searches were performed in the databases "PubMed", "Web of Science", "LILACS" and "ScienceDirect" using the following search terms: 2019-nCoV, covid-19, SARS-CoV-2, pregnant, pregnancy, birth, fetal, neonatal, outcomes, complications and adverse. The studies involved 226 pregnant women diagnosed with COVID-19 and 174 healthy pregnant women. Among the 226 pregnant women with COVID-19, there was 01 intrauterine fetal death and 16 remained pregnant until the end of the respective studies. Thus, 209 pregnant women with COVID-19 evolved for childbirth, resulting in 212 live births. Of these, 127 (59.9%) were born by cesarean delivery, 38 (17.9%) were born at